Effects of Ultrasound-Guided Thoracic Paravertebral Nerve Block Combined with Perineural or IV Dexmedetomidine on Acute and Chronic Pain After Thoracoscopic Resection of Lung Lesions: A Double-Blind Randomized Trial - Chen Z; Gao C; Zhang Y; Gao Y; Zhang L; Zhao S; Zhang H; Zhao X; Jin Y (Dove Medical Press, 2024)
Zheping Chen,1,* Changli Gao,1,2,* Yingchao Zhang,1,3 Yongxu Gao,1,4 Le Zhang,1 Shanshan Zhao,1 He Zhang,1 Xin Zhao,1 Yanwu Jin1 1Department of Anesthesiology, the Second Hospital, Cheeloo College of Medicine, Shandong University, Jinan, People's Republic of China; 2Department of Anesthesiology, Laoling People Hospital, Laoling, People's Republic of China; 3Department of Anesthesiology, Shouguang People Hospital, Weifang, People's Republic of China; 4Department of Anesthesiology, Jinan Third People's Hospital, Laoling, People's Republic of China*These authors contributed equally to this workCorrespondence: Yanwu Jin, Department of Anesthesiology, the Second Hospital, Cheeloo College of Medicine, Shandong University, 247 Bei Yuan Street, Jinan, 250033, People's Republic of China, Tel +86-17660085535, Email jinyanwu_aa@163.comBackground: Thoracic paravertebral block (TPVB) analgesia can be prolonged by local anesthetic adjuvants such as dexmedetomidine. This study aimed to evaluate the two administration routes of dexmedetomidine on acute pain and chronic neuropathic pain (NeuP) prevention compared with no dexmedetomidine.Methods: A total of 216 patients were randomized to receive TPVB using 0.4% ropivacaine alone (R Group), with perineural dexmedetomidine 0.5 μg·kg− 1 (RD0.5 Group) or 1.0 μg·kg− 1 (RD1.0 Group), or intravenous (IV) dexmedetomidine 0.5 μg·kg− 1·h− 1 (RDiv Group). The primary outcome was the incidence of chronic NeuP, defined as a Leeds Assessment of Neuropathic Symptoms and Signs (LANSS) pain score > 12 points at 3-month after surgery.Results: (1) For the primary outcome, RD0.5 Group and RD1.0 Group demonstrated a decreased incidence of chronic NeuP at 3-month after surgery; (2) Compared with R Group, RDiv Group, RD0.5 Group, and RD1.0 Group can reduce VAS scores at rest and movement and Prince-Henry Pain scores at 12 and 24-h after surgery, the consumption of oral morphine equivalent (OME) and improve QOD-15 at POD1; (3) Compared with RDiv Group, RD0.5 Group and RD1.0 Group can reduce VAS scores at rest and movement and Prince-Henry Pain scores at 12 and 24-h after surgery, the consumption of postoperative OME and improve QOD-15 at POD1; (4) Compared with RD0.5 Group, RD1.0 Group effectively reduced VAS scores at rest at 12 and 24-h after surgery, VAS scores in movement and Prince-Henry Pain scores at 12-h after surgery. However, RD1.0 Group showed an increased incidence of drowsiness.Conclusion: Perineural or IV dexmedetomidine are similarly effective in reducing acute pain, but only perineural dexmedetomidine reduced chronic NeuP. Moreover, considering postoperative complications such as drowsiness, perineural dexmedetomidine (0.5 μg·kg− 1) may be a more appropriate choice.Clinical Trial Registration: Chinese Clinical Trial Registry (ChiCTR2200058982).Keywords: dexmedetomidine, thoracic paravertebral nerve block, neuropathic pain, thoracoscopic surgery